ANALYSIS OF CHARACTER EDUCATIONAL VALUES IN HAIKYUU !! TO THE TOP ANIME BY HARUICHI FURUDATE AND ITS RELEVANCE TO ISLAMIC RELIGIOUS EDUCATION - Razaqna, Wilda; Satriyadi (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2024)
This study aims to uncover and understand the values of character education, namely religious values, practical values, scientific values, moral values, and social values in the anime Haikyuu!! To The Top by Haruichi Furudate. The value of character education is very important for humanity. Messages and values of character education can be developed and obtained from various learning media, one of which is anime films. Anime Haikyuu!! To The Top is one of the works that contains the values of character education, so it needs to be analyzed against Islamic education which can function as the instillation of Islamic character values. This study uses a qualitative approach with the type of library research, using content analysis as a research procedure that produces descriptive data in the form of written words rather than numbers. Therefore, this study contains data citations to provide a report presentation. From the results study so can concluded that values education the characters contained in the anime Haikyuu !! To The Top work Haruichi Furudate globally divided​ become five : Practical values include character values creative , value character Work hard , value character care social , values character religious and values disciplined character . Faith values include religious character values. Moral values include moral values . character not quite enough answer , value character care social and values character Discipline . Social values include the character values of appreciating achievement, the character values of social concern, the character values of loving peace, and the character values of being friendly/communicative. Scientific values include the character values of curiosity.